Existence of Two Form of L Protein of Newcastle Disease Virus Isolates Due to a Compensatory Mutation in Domain V - Kusumaningtyas, Eni; Tan, Wen Siang; Zamrod, Zulkeflie; Eshaghi, Majid; Yusoff, Khatijah (Springer Wien, 2004)
Summary. Nucleotide sequence comparison of the L gene of the Malaysian neurotropic-viscerotropic velogenic NDV strain AF2240 with other NDV strains revealed a single nucleotide insertion at position 3870. This mutation is compensated by a nucleotide deletion downstream at position 3958 which results in two forms of the L proteins containing a 30-amino acid substitution in Domain V. This compensatory mutation this does not correlate with the pathogenicity of the viral strains but is may affect the viral replication as Domain V is believed to play an important role in the replication of paramyxoviruses.